Fiscal prices of the fifth of the gold. Lima, XVI-XVIII centuries - Luque Luque, Juvenal (2009)
The present text is a study based on countable sources of the Lima Real Treasure that has made possible the systematic tracking of the fiscal prices of gold. In this text one clarifies some the mysteries that are behind the called positions fifth real ones and needs plus some topics the same. It is a contribution that extends plus the knowledge of the colonial mining and the problematic one of the fifth golden one and his payment to the Be in favor of concept of taxes in currency sealed instead of physical gold.